Performance Analysis Smart-Shoes To Measure the Pulse in Dorsalis Pedis Artery - Akhmad Afrizal Rizqi; Aripriharta; Ilham Ari Elbaith Zaeni (Fidelity : Jurnal Teknik Elektro, 2023)
Wearable device has grown in popularity in recent years. This article presents the performance of smart shoes as a biomedical device that can be used to capture heart rate signals from the dorsalis pedis artery on the leg. In general, heart rate is measured from the arteries located in the chest, hands, fingertips, and ears or neck. Even though the pulse from the dorsalis pedis has a smaller amplitude compared to other arterial locations, the sensor is integrated on smart shoes can catch the sign al from the dorsalis pedis pulse. Research is intended to analyze lifetime and accuracy smart shoes. The experiment was carried out by 30 healthy male and female volunteers aged 20 - 25 years. The results obtained indicate that the sensor smart shoes can measure the dorsalis pedis pulse and has an average error rate of 9.28% compared to a digital sphygmomanometer. Based on the results of energy consumption analysis, smart shoes in this study has a lifetime of up to 25.86 hours using a 1100 mAh battery.